2020
DOI: 10.1105/tpc.19.00666
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Exon Junction Complex Footprints in the RNA Degradome Mark mRNA Degradation before Steady State Translation

Abstract: Exon junction complexes (EJCs) are deposited on mRNAs during splicing and displaced by ribosomes during the pioneer round of translation. Nonsense-mediated mRNA decay (NMD) degrades EJC-bound mRNA, but the lack of suitable methodology has prevented the identification of other degradation pathways. Here, we show that the RNA degradomes of Arabidopsis (Arabidopsis thaliana), rice (Oryza sativa), worm (Caenorhabditis elegans), and human (Homo sapiens) cells exhibit an enrichment of 59 monophosphate (59P) ends of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 74 publications
3
24
1
Order By: Relevance
“…Although initially considered independent events, multiple evidence has now demonstrated that translation and mRNA decay are interconnected processes and that co-translational mRNA degradation is a general phenomenon (2)(3)(4)(5). The interaction between the translation and decay machinery occurs so close that the positions of 5'P co-translational mRNA degradation intermediates can be used as a proxy for ribosome dynamics, as we and others have shown in yeast (6)(7)(8) and plants (4,9,10). In particular, XRN1driven 5'-3' mRNA degradation is linked to the movement of the last translating ribosome allowing to obtain an in vivo footprint of the ribosome position.…”
Section: Introductionmentioning
confidence: 89%
“…Although initially considered independent events, multiple evidence has now demonstrated that translation and mRNA decay are interconnected processes and that co-translational mRNA degradation is a general phenomenon (2)(3)(4)(5). The interaction between the translation and decay machinery occurs so close that the positions of 5'P co-translational mRNA degradation intermediates can be used as a proxy for ribosome dynamics, as we and others have shown in yeast (6)(7)(8) and plants (4,9,10). In particular, XRN1driven 5'-3' mRNA degradation is linked to the movement of the last translating ribosome allowing to obtain an in vivo footprint of the ribosome position.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, exon junction complexes (EJCs) deposited upstream of the exon-exon junctions on mRNAs during splicing and removed upon the first round of translation, can protect mRNAs from degradation. In the current issue, Lee et al (2020) show that the RNA degradome contains EJC footprints that mark mRNAs degraded during or before the pioneer round of translation. EJC footprints were prevalent in targets of nonsense-mediated decay (NMD) pathway, but were also present in some mRNAs degraded through miRNA-mediated cleavage.…”
mentioning
confidence: 94%
“…EJC footprints were prevalent in targets of nonsense-mediated decay (NMD) pathway, but were also present in some mRNAs degraded through miRNA-mediated cleavage. Lee et al (2020) analyzed RNA degradome data for 5'P end occurrence and found that it was relatively higher in the regions 25-30 nt upstream of the 3' ends of exons, where EJCs are canonically positioned. This pattern was present in Arabidopsis, rice, human, and worm datasets, but not in budding yeast that lacks EJCs, suggesting that the 5'P peaks corresponded to 5' termini of RNA degradation intermediates protected from degradation by EJCs.…”
mentioning
confidence: 99%
See 2 more Smart Citations